Modeling current and voltage peaks generation in complementary resistive switching devices. (September 2021) - Blonkowski, S.; Labalette, M.; Jeannot, S.; Ecoffey, S.; Souifi, A.; Drouin, D.
Abstract: We propose a physical model of complementary resistive switching (CRS) based on the disruption and reformation process of a metallic filament inside each Oxyde Resistive Random Access Memory (OxRRAM) composing the CRS. The driving forces involved in this process are electromigration forces, electron phonon coupling and joule heating. The model accounts well for the experimental CRS current voltage characteristics. The stability of the CRS states and the CRS operation in pulse regime, including the current and voltage peaks generation are discussed.